The exploration Batak Toba culture based on Schwartz Basic Values Theory: A descriptive analysis of cultural value Dalihan Na Tolu - Sinaga, Nurtaty (Talenta Publisher, 2024)
Indonesia is a country rich in ethnic and cultural diversity, one of which is the Batak Toba culture. Batak Toba culture places great importance on the philosophy of Dalihan Na Tolu, a traditional framework that emphasizes social harmony and respect. This study explores the relationship between Schwartz’s fundamental human values and the philosophy of Dalihan Na Tolu in Batak Toba culture. The research respondents comprised 143 Batak Toba individuals aged between 16 and 29 years, 44 men and 99 women. The instrument used was the Portrait Values Questionnaire(PVQ-40), adapted to the Indonesian context. The research found that the highest value among Batak Toba people is universalism, with self-transcendence being the dominant value orientation. These fundamental values of universalism and self-transcendence are strongly reflected in the Dalihan Na Tolu philosophy, which emphasizes the importance of maintaining harmony and balance between humans and nature.